Towards a critical pedagogy of place for environmental conservation - Ajaps, Sandra; Forh Mbah, Marcellus (Environmental Education Research, 2022)
Keywords: _z:class:countries; _z:class:themes; oa:keyword:critical pedagogy; oa:keyword:environmental conservation; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12997 Experiential Education and Adventure Therapy; oa:topic:T14007 Place-Based Education in Rural Communities; openalex:n:1; openalex:yes

Deconstructing Community-Based Research for Sustainable Development: The Role of Indigenous Knowledge Holders - Ajaps, Sandra; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Keywords: _z:class:countries; _z:class:themes

Indigenous Methodologies, Research and Practices for Sustainable Development - Mbah, Marcellus F.; Leal Filho, Walter; Ajaps, Sandra (Springer Nature, 2022)
Keywords: _z:class:countries; _z:class:themes

Envisioning the Indigenised university for sustainable development - Mbah, Marcellus Forh; Ajaps, Sandra; Johnson, Ane Turner; Yaffa, Sidat (International Journal of Sustainability in Higher Education, 2022)
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenised university; oa:keyword:sustainable development; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Envisioning the Indigenised university for sustainable development - Mbah, Marcellus Forh; Ajaps, Sandra; Johnson, Ane Turner; Yaffa, Sidat (International Journal of Sustainability in Higher Education, 2022)
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indigenised university; oa:keyword:sustainable development; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; oa:topic:T11835 Sustainability Education in Higher Education Institutions; openalex:n:1; openalex:yes

Decolonisation of Research Methodologies for Sustainable Development in Indigenous Settings - Mbah, Marcellus F.; Bailey, Megan (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Keywords: _z:class:countries; _z:class:themes

Public Health Education in Africa: The Case of Epistemic (in) Justice and Indigenous Health Systems - Orjinta, Amarachi Jane-Frances; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
Keywords: _z:class:countries; _z:class:themes

Towards an Integrated Approach to Climate Change Education in Tanzania: The Role of Indigenous Knowledge Systems - Mugabe, Paschal Arsein; Mbah, Marcellus; Apollo, Abigael; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
There have been many efforts globally toward fighting climate change; including international agreements, conferences, research, policies, forums, etc. In addition to these efforts, climate change education has recently emerged as an essential capacity-building tool to curb the climate crisis. However, development practitioners from the Global South have cited limitations with climate change education due to the dominance of Eurocentric epistemologies over indigenous knowledge (IK) approaches. This study therefore advocates for the integration of indigenous knowledge into climate change education in Tanzania for achieving a sustainable environment. Seventy documents, including peer-reviewed papers, reports from corporate institutions, policy briefs, proceedings and other grey literature were reviewed. We establish that IK systems are not integrated into CCE in Tanzania. However, we find opportunities for integration due to the evidence of the existing CCE efforts and potential complementary indigenous practices. By identifying, documenting, and validating indigenous knowledge and merging this knowledge with scientific insights, the fostering of an integrated approach to combat the enduring effects of climate change can be evidenced.
Keywords: C:Tanzania; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:indigenous knowledge systems; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:n:1; openalex:yes